Baseline reward circuitry activity and trait reward responsiveness predict expression of opioid analgesia in healthy subjects. - Wanigasekera, V; Lee, M; Rogers, R; Kong, Y; Leknes, S; Andersson, J; Tracey, I (2012)
Variability in opioid analgesia has been attributed to many factors. For example, genetic variability of the μ-opioid receptor (MOR)-encoding gene introduces variability in MOR function and endogenous opioid neurotransmission. Emerging evidence suggests that personality trait related to the experience of reward is linked to endogenous opioid neurotransmission. We hypothesized that opioid-induced behavioral analgesia would be predicted by the trait reward responsiveness (RWR) and the response of the brain reward circuitry to noxious stimuli at baseline before opioid administration. In healthy volunteers using functional magnetic resonance imaging and the μ-opioid agonist remifentanil, we found that the magnitude of behavioral opioid analgesia is positively correlated with the trait RWR and predicted by the neuronal response to painful noxious stimuli before infusion in key structures of the reward circuitry, such as the orbitofrontal cortex, nucleus accumbens, and the ventral tegmental area. These findings highlight the role of the brain reward circuitry in the expression of behavioral opioid analgesia. We also show a positive correlation between behavioral opioid analgesia and opioid-induced suppression of neuronal responses to noxious stimuli in key structures of the descending pain modulatory system (amygdala, periaqueductal gray, and rostral-ventromedial medulla), as well as the hippocampus. Further, these activity changes were predicted by the preinfusion period neuronal response to noxious stimuli within the ventral tegmentum. These results support the notion of future imaging-based subject-stratification paradigms that can guide therapeutic decisions.